2022
DOI: 10.3389/fphar.2022.956220
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances on development of p21-activated kinase 4 inhibitors as anti-tumor agents

Abstract: The p21-activated kinase 4 (PAK4) is a member of the PAKs family. It is overexpressed in multiple tumor tissues. Pharmacological inhibition of PAK4 attenuates proliferation, migration, and invasion of cancer cells. Recent studies revealed that inhibition of PAK4 sensitizes immunotherapy which has been extensively exploited as a new strategy to treat cancer. In the past few years, a large number of PAK4 inhibitors have been reported. Of note, the allosteric inhibitor KPT-9274 has been tested in phase Ⅰ clinic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 91 publications
(133 reference statements)
0
9
0
Order By: Relevance
“…Given its short half-life and mechanism of action, it is unlikely that the KPT-9274 affected the normal B-cell population. 45,46 In mouse models, the SUMO-activating enzyme inhibitor TAK-981 did induce transient decreases in normal B-cell populations in the spleens and blood of mice, but these rapidly recovered within 4 days after discontinuation of treatment. 47 It is therefore conceivable that the TAK-981 acted in an additive or synergistic manner with 1E4-cIgGB to selectively deplete B-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given its short half-life and mechanism of action, it is unlikely that the KPT-9274 affected the normal B-cell population. 45,46 In mouse models, the SUMO-activating enzyme inhibitor TAK-981 did induce transient decreases in normal B-cell populations in the spleens and blood of mice, but these rapidly recovered within 4 days after discontinuation of treatment. 47 It is therefore conceivable that the TAK-981 acted in an additive or synergistic manner with 1E4-cIgGB to selectively deplete B-cells.…”
Section: Discussionmentioning
confidence: 99%
“…PAK4 was involved in resistance to tamoxifen of breast cancer cells [ 11 ] and resistance to gemcitabine of pancreatic cancer cells [ 12 ]. Inhibition of PAK4 with specific inhibitors has been shown to inhibit the proliferation of cancer cells [ 10 ] and induced restoration of sensitivity to anticancer agents [ 11 , 12 ]. Moreover, as more evidence emerges regarding the role of PAK4 in the immune evasion of cancer cells, research has evaluated the efficacy of a combination treatment of PAK4 inhibition and immune checkpoint inhibitors [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of PAK4 in cancer progression has been suggested by its role in regulating various aspects of cancer cell behavior, such as proliferation, invasiveness, angiogenesis, metabolic reprogramming, and immune evasion [ 3 , 4 ]. In addition, inhibition of PAK4 was presented as a therapeutic strategy for human cancers [ 3 , 10 ] and PAK4 inhibitors showed antitumor activity in the breast [ 11 ], pancreas [ 12 ], and colorectal cancers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not sufficient for competitive inhibitors whose Studies in recent years showed that PAK4 inhibitors can inhibit its expression, thus preventing tumor growth, inducing tumor regression, and avoiding tumor cell metastasis, which has a good effect on the treatment of cancers [17]. PAK4 inhibitors can be divided into ATP-competitive inhibitors and non-competitive allosteric inhibitors depending on their binding positions and modes of action [18]. Among them, the study on the pyrrolopyrazole inhibitor PF-3758309 is relatively early.…”
Section: Introductionmentioning
confidence: 99%